2021
DOI: 10.1038/s41420-021-00688-6
|View full text |Cite
|
Sign up to set email alerts
|

METTL3 improves cardiomyocyte proliferation upon myocardial infarction via upregulating miR-17-3p in a DGCR8-dependent manner

Abstract: Myocardial infarction (MI), one of the most severe types of heart attack, exerts a strong negative effect on heart muscle by causing a massive and rapid loss of cardiomyocytes. However, the existing therapies do little to improve cardiac regeneration. Due to the role of methyltransferase-like 3 (METTL3) in the physiological proliferation of cardiomyocytes, we aimed to determine whether METTL3 could also promote cardiomyocyte proliferation under pathological conditions and to elucidate the underlying mechanism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
0
16
1
Order By: Relevance
“…In fact, similar contradictory results regarding the role of METTL3 have been observed in other cardiovascular diseases. For example, a recent study discovered that METTL3 knockdown could promote CM proliferation [31], while in another METTL3 was proven to activate the proliferation of CMs [32], which highly suggested that the biological function of m6A modification is extremely complex in the cardiac system. Our results were based on Ang-II stimulation, which mainly exerts its function through the angiotensin type 1 receptor (AT1R), while phenylephrine compound predominantly acts as α(1) adrenergic receptor agonist [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, similar contradictory results regarding the role of METTL3 have been observed in other cardiovascular diseases. For example, a recent study discovered that METTL3 knockdown could promote CM proliferation [31], while in another METTL3 was proven to activate the proliferation of CMs [32], which highly suggested that the biological function of m6A modification is extremely complex in the cardiac system. Our results were based on Ang-II stimulation, which mainly exerts its function through the angiotensin type 1 receptor (AT1R), while phenylephrine compound predominantly acts as α(1) adrenergic receptor agonist [33,34].…”
Section: Discussionmentioning
confidence: 99%
“… 55 In line with this, METTL3 overexpression has recently been unveiled to also promote neonatal rat cardiomyocyte proliferation after hypoxia and to ameliorate ischemic myocardial damage in adult rats by promoting pri-miR-17-3p maturation in a m 6 A-DGCR8 microprocessor complex subunit-(DGCR8)-dependent manner. 147 …”
Section: N 6 -Methyladenosine and A-to-i Modificat...mentioning
confidence: 99%
“…55 In line with this, METTL3 overexpression has recently been unveiled to also promote neonatal rat cardiomyocyte proliferation after hypoxia and to ameliorate ischemic myocardial damage in adult rats by promoting pri-miR-17-3p maturation in a m 6 A-DGCR8 microprocessor complex subunit-(DGCR8)-dependent manner. 147 On the other hand, in mice, global METTL3 knockout has been described to enhance regeneration-related markers and enhance cardiac function after MI via m 6 A-dependently inhibited pri-miR-143-3p maturation. 140 The muscle-specific cardiac miRNA, miR-133a, was found to harbor a complementary motif CCUG for the DR-m 6 A-CH m 6 A consensus sequence within its seed sequence, thus making it exquisitely prone to bind m 6 A-modified mRNAs.…”
Section: A-to-i Editingmentioning
confidence: 99%
See 2 more Smart Citations